Extension agents and sustainable cocoa farming: a case study of extension agents in Sabah state, Malaysia - Tiraieyari, Neda; Hamzah, Azimi; Abu Samah, Bahaman (Canadian Center of Science and Education, 2014)
Cocoa has been commercially planted in Malaysia since the 1950s. Over the years, the planting area has gradually reduced, which has resulted in the need to import cocoa beans to sustain the local grindings requirement. The Malaysian Cocoa Board (MCB) has introduced extension programmes to cocoa farmers to encourage sustainable farming of cocoa in the country. This study assessed the perception, knowledge, attitudes, and value of agricultural extension agents towards sustainable cocoa farming in Sabah State, Malaysia. Data were collected from extension agents working for the Malaysian Cocoa Board. A questionnaire was administered to all the front-line extension agents who deal directly with cocoa farmers. Findings revealed that cocoa extension agents’ perception, knowledge, attitudes, and value towards the concept of sustainable cocoa farming is favourable. In fact, they strongly support the concept. A significant relationship exists between knowledge on Sustainable Cocoa Farming (SCF) and their attitude towards the concept (r = 0.465). Perception also significantly correlates with the attitude of the agents (r = 0.425). The study concluded that policymakers should include SCF in training. Extension agents’ positive perceptions regarding selected sustainable cocoa farming have implications for in-service training for agricultural extension agents in the east of Malaysia to increase their specific knowledge in SCF. In addition, although cocoa extension agents possess general knowledge on the concept, further training on the application of SCF is highly recommended.